The Vision of the Balkans in Musical Culture: Between Viennese Operetta and Eurovision - Piotrowska, Anna G. (Journal of religion & society. Supplement, 2019)
This article addresses the representation and conceptualization of the Balkans in musical culture since the nineteenth century. It argues that typical strategies of (self-)exoticizing and the approximation of dominant musical tendencies promoted Balkan musical uniqueness by underlining its naturalness and authenticity and are part of the legacy of nineteenth-century ideological and musicological theories. A few carefully selected examples, namely, Viennese operettas, popular films by Emir Kusturica, and Balkan performances in the Eurovision Song Contest (specifically the 2007 winner Marija Šerović’s “Molitva” [“Prayer”] which transcended religious and ethnic boundaries in its appeal), will demonstrate the primary types of narratives used to depict Balkan music to the outside world.